DEVELOPING AUDIOBOOK TO TEACH LISTENING COMPREHENSION FOR ELEVENTH GRADERS OF SENIOR HIGH SCHOOL - Herlyanti, Putri; Suhartono, Luwandi; Sumarni, Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The goal of this study was to develop an audiobook as course materialfor teaching and developing listening comprehension. This wasdevelopment research, and the materials were designed using theADDIE procedure. Despite this, just three phases of the research wereimplemented: analyzing, designing, and developing. The finishedproduct for teaching and learning listening comprehension was Let"™sListen: Audiobook. The conduct the analysis phase, the researcherinterviewed an English instructor from SMA Negeri 9 Pontianak.Audacity was used to build the Let"™s Listen Audiobook, while Canvawas used as the assisting software. During the development process,the researcher utilized an internal evaluation to guarantee that theproduct is useable. Let"™s Listen: Audiobook passed the internal reviewprocess with excellent grades, meeting all of the objectives, content,and media options. It was determined that by simplifying the partsfrom Let"™s Listen: Audiobook, the product may be applied to teach andlearn listening comprehension.